ANALISIS KEMAMPUAN LITERASI PESERTA DIDIK DALAM PEMBELAJARAN MATEMATIKA DITINJAU DARI GAYA BELAJAR - Nikmah, Siti Maghfirotun; Fauziyah, Nur (Universitas Jenderal Soedirman, 2024)
ABSTRACT. This research is a qualitative descriptive study, which aims to describe the analysis of the mathematical literacy abilities of students with high mathematical abilities in terms of learning styles. This research was carried out in one of the state junior high schools in the Gresik area, class VII in the 2023/2024 even semester academic year. The subjects of this research consisted of three students, namely one student had a visual learning style, one student had an auditory learning style and one student had a kinesthetic learning style with each student having high mathematical abilities. The data collection techniques used in this research were questionnaires, tests and interviews. The analysis technique used is the Miles and Huberman model which includes data reduction, data presentation and drawing conclusions. The results of the research analysis and discussion of three subjects who have high mathematical abilities in terms of learning styles are able to solve problems based on mathematical literacy. However, in working on the questions that have been given to the three subjects with high mathematical abilities in terms of learning styles at State Middle Schools in the Gresik region, it shows that students with high mathematical abilities with a visual learning style have better mathematical literacy skills in working on questions than students with kinesthetic and auditory learning styles high mathematical abilities.Keywords:: Mathematical Literacy Ability, Visual Learning Style, Auditory Learning Style, Kinesthetic Learning Style. ABSTRAK. Penelitian ini merupakan deskriptif kualitatif, yang bertujuan untuk mendeskripsikan analisis kemampuan literasi matematika peserta didik berkemampuan matematika tinggi ditinjau dari gaya belajar. Penelitian ini dilaksanakan di salah satu SMP negeri di wilayah Gresik kelas VII pada tahun ajaran 2023/2024 semester genap. Subjek penelitian ini terdiri dari tiga peserta didik yaitu satu peserta didik memiliki gaya belajar visual, satu peserta didik memiliki gaya belajar auditori dan satu peserta didik memiliki gaya belajar kinestetik dengan masing masing peserta didik mempunyai kemampuan matematika tinggi. Teknik pengumpulan data yang digunakan dalam penelitian ini adalah angket, tes, dan wawancara. Teknik analisis yang digunakan adalah model Miles and Huberman yang meliputi reduksi data, penyajian data, dan penarikan kesimpulan. Hasil analisis dan pembahasan penelitian dari tiga subjek yang memiliki kemampuan matematika tinggi ditinjau dari gaya belajar mampu menyelesaikan soal berbasis literasi matematika. Tetapi dalam pengerjaan soal yang sudah berikan kepada ketiga subjek kemampuan matematika tinggi yang ditinjau dari gaya belajar di SMP Negeri wilayah Gresik menunjukkan bahwa peserta didik dengan kemampuan matematika tinggi dengan gaya belajar visual memiliki kemampuan literasi matematika yang lebih baik dalam mengerjakan soal dari pada peserta didik dengan gaya belajar kinestetik dan auditori kemampuan matematika tinggi.Kata Kunci: Kemampuan Literasi Matematis, Gaya Belajar Visual, Gaya Belajar Auditori, Gaya Belajar Kinestetik.